2020
DOI: 10.3390/biology9080218
|View full text |Cite
|
Sign up to set email alerts
|

Toad Venom Antiproliferative Activities on Metastatic Melanoma: Bio-Guided Fractionation and Screening of the Compounds of Two Different Venoms

Abstract: Melanoma is the most common cancer in young adults, with a constantly increasing incidence. Metastatic melanoma is a very aggressive cancer with a 5-year survival rate of about 22−25%. This is, in most cases, due to a lack of therapies which are effective on the long term. Hence, it is crucial to find new therapeutic agents to increase patient survival. Toad venoms are a rich source of potentially pharmaceutically active compounds and studies have highlighted their possible effect on cancer cells. We focused o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 57 publications
2
7
0
Order By: Relevance
“…Several studies on the composition of PGS have been undertaken with the methanol soluble fraction of the crude venom. Recently, the effect was reported of PGS of Bufo bufo and R. marina on metastatic melanoma, finding that the bufadienolide bufalin was the best antiproliferative agent in the samples [53]. Sinhorin, et al [54] described the composition of the Amazonian Rhinella margaritifera PGS and reported argininyl diacids, bufotalin, and cinobufagin argininyl diacids as well as the bufadienolides bufotalin, cinobufagin, and telocinobufagin as main compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on the composition of PGS have been undertaken with the methanol soluble fraction of the crude venom. Recently, the effect was reported of PGS of Bufo bufo and R. marina on metastatic melanoma, finding that the bufadienolide bufalin was the best antiproliferative agent in the samples [53]. Sinhorin, et al [54] described the composition of the Amazonian Rhinella margaritifera PGS and reported argininyl diacids, bufotalin, and cinobufagin argininyl diacids as well as the bufadienolides bufotalin, cinobufagin, and telocinobufagin as main compounds.…”
Section: Discussionmentioning
confidence: 99%
“…While many studies have demonstrated that Fli1 is a pro-cancer factor [ 68 , 69 ], CS including MBG are becoming attractive anti-cancer drug candidates [ 70 , 71 ]. It is generally accepted that PE is associated with a low risk of cancer, which is not surprising considering that endogenous levels of MBG and other CS are dramatically increased in PE patients [ 27 , 28 ] and therefore suppress the growth of tumors in vivo and in vitro [ 72 , 73 , 74 ]. Therefore, theoretically, in cancer patients and experimental animals, MBG should suppress the levels of Fli1, an oncogene.…”
Section: Interaction Of Cs and Fli1 And A Hint For Cancermentioning
confidence: 99%
“…While many studies demonstrate that Fli1 is a pro-cancer factor [57,58], CS, including MBG, are becoming attractive anticancer drugs [59,60]. It is generally accepted that PE is associated with a low risk of cancer, which is not surprising considering that endogenous levels of MBG and other CS are dramatically increased in PE patients [27,28] and therefore suppress the growth of tumors in vivo and in vitro [61,62,63]. Therefore, theoretically, in cancer, patients and experimental animals, MBG should suppress levels of Fli1, an oncogene.…”
Section: Interaction Of Cs and Fli1 And A Hint For Cancermentioning
confidence: 99%
“…Proscillaridin A was identified as a potential treatment compound with IC50 values ranging from 0.007 μM to 0.55 μM in various tumor types [87]. Importantly, the number of studies in which bufadienolides were used as an in-vitro anti-cancer treatment is heightened, and bufadienolide inhibitors of the Na/K-ATPase are used in vitro and in vivo include MBG [59,60], bufalin [88,89], cinobufagin [90], resibufagenin [91], proscillaridin A [92], gamabufotalin [93], and 1α,2α-Epoxyscillirosidine [94]. Analyzing experiments and clinical data it is obvious that MBG and other Na/K-ATPase inhibitors hold promise to treat cancer, and following anti-CS antibody treatment to PE patients we must expect a rise of Fli1 and be alert.…”
Section: Interaction Of Cs and Fli1 And A Hint For Cancermentioning
confidence: 99%